FINANCIAL TECHNOLOGY (FINTECH), LITERASI KEUANGAN, INKLUSI KEUANGAN DAN KINERJA UMKM DI KOTA SURABAYA - Jasmine Shelomita Putri Hasibuan; Kholidiah Kholidiah (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to examine and analyze the effect of Financial Technology (Fintech), financial literacy, and financial inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Surabaya City. The development of digital technology has driven changes in public transaction behavior and requires MSME actors to adapt through the utilization of technology-based financial services, improvement of financial knowledge, and broader access to formal financial services. This study employed a quantitative approach using a survey method through the distribution of questionnaires to MSME owners in Surabaya City who had utilized Financial Technology (Fintech) services. The sampling technique used was purposive sampling, with a total of 155 MSME respondents. The collected data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 25. The results indicate that Financial Technology (Fintech) has a positive and significant effect on MSME performance. Financial literacy also has a positive and significant effect on MSME performance. Furthermore, financial inclusion has a positive and significant effect on MSME performance. Simultaneously, Financial Technology (Fintech), financial literacy, and financial inclusion have a significant effect on the performance of MSMEs in Surabaya City.